2006
DOI: 10.1111/j.1744-7909.2006.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Gas Exchange, Abscisic Acid, and Calmodulin Response to Salt Stress in Three Poplars

Abstract: In the present study, we investigated the effects of increasing salinity on growth, gas exchange, abscisic acid (ABA), calmodulin (CaM), and the relevance to salt tolerance in seedlings of Populus euphratica Oliv. and cuttings of P. "pupularis 35-44" (P. popularis) and P. × euramericana cv. I-214 (P. cv. Italica). The relative growth rates of shoot height (RGR H ) for P. cv. Italica and P. popularis were severely reduced by increasing salt stress, whereas the growth reduction was relatively less in P. euphrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 40 publications
3
20
2
Order By: Relevance
“…These high levels in leaves were maintained for 1 week and further increased (fourfold) during the second week. This observation with the salt-sensitive grey poplar is not consistent with the hypothesis by Chang et al (2006) predicting that continuously high ABA levels are important for salt resistance of P. euphratica.…”
Section: Expressioncontrasting
confidence: 74%
See 3 more Smart Citations
“…These high levels in leaves were maintained for 1 week and further increased (fourfold) during the second week. This observation with the salt-sensitive grey poplar is not consistent with the hypothesis by Chang et al (2006) predicting that continuously high ABA levels are important for salt resistance of P. euphratica.…”
Section: Expressioncontrasting
confidence: 74%
“…9). In contrast to the salt-sensitive poplar investigated previously (Chang et al 2006), grey poplar throughout the experiment exhibited similar ABA values in leaves to those measured in the salt tolerant P. euphratica (Chang et al 2006). These high levels in leaves were maintained for 1 week and further increased (fourfold) during the second week.…”
Section: Expressionsupporting
confidence: 51%
See 2 more Smart Citations
“…However, the best known functions of ABA are related to the recruitment of stress-signaling networks. ABA accumulates in plants exposed to salt stress (Chen et al, 2003;Chang et al, 2006), and deficiency makes plants more stress sensitive (Xiong et al, 2002). Genevestigator analysis of our PiRGs showed that many stress-related genes were activated by ABA or salt in Arabidopsis (RD26, LPT family protein, aldehyde dehydrogenase 7B4, galactinol synthase, phospholipase 2A, photoassimilate-responsive protein, WRKY40, and glutathione S-transferase), whereas a common feature of genes in the category Signaling was that their transcript abundance decreased in response to ABA (Supplemental Fig.…”
Section: Ems Lead To Activation Of Defenses and Prime Roots Formentioning
confidence: 99%